Norisoboldine, an alkaloid from Radix linderae, inhibits NFAT activation and attenuates 2, 4-dinitrofluorobenzene-induced dermatitis in mice. (2nd September 2016) - Gao, Shuang; Li, Wencai; Lin, Guochao; Liu, Guangrong; Deng, Wenjuan; Zhai, Chuntao; Bian, Chunliang; He, Gaiying; Hu, Zhenlin
Abstract: Context: The nuclear factor of activated T-cells (NFAT) is a family of transcription factors, essential for T-cell activation. Norisoboldine (NOR), an isoquinoline alkaloid from Radix linderae, has been demonstrated to possess anti-inflammatory activity. Objective: This study examines NOR's effect on NFAT activation and its therapeutic potential for atopic dermatitis (AD). Materials and methods: The transcriptional activity of NFAT was examined with luciferase reporter assay, using K562-luc cells, stimulated with 20 ng/mL PMA plus 1 μM ionomycin. NFAT dephosphorylation was examined by immuno-blotting in K562-luc cells and Jurkat cells. Interleukin-2 (IL-2) expression in Jurkat cells was examined by real-time PCR. A mouse model of dermatitis, induced by 2, 4-dinitrochlorobenzene (DNCB), was used to test NOR's therapeutic potential for AD. Results: NOR, dose-dependently, inhibited PMA and ionomycin-induced NFAT reporter gene expression in K562-luc cells in the range of 2–50 μM. NOR also inhibited PMA and ionomycin-induced NFAT dephosphorylation in K562-luc cells and Jurkat cells. Consequently, NOR suppressed PMA plus ionomycin-induced IL-2 expression in Jurkat cells. The administration of NOR (10 mg/kg, i.p.), alleviated DNCB-induced dermatitis in mice, by the reduction of ear swelling and attenuation of inflammatory infiltration into ear tissue. Moreover, mRNA levels of INF-γ, TNF-α, IL-4 and IL-6 in ears of NOR-treated mice were reduced by 78.4, 77.8, 72.3 and 73.9%, respectively, compared with untreated controls. Discussion and conclusion: This study demonstrates that NOR inhibits NFAT activation in T-cells and alleviates AD-like inflammatory reaction in a DNCB-induced dermatitis model, highlighting NOR as a potential therapeutic agent for AD.